Compilation of IMPACT training presentations - Sulser, Timothy B.; Mishra, Abhijeet; Gabriel, Sherwin; Thomas, Timothy S.; Robertson, Richard D. (International Food Policy Research Institute, 2025)
Presentation titles: 1. Introduction to IFPRI’s IMPACT modeling framework; 2. Practical exercise with IMPACT outputs; 3. Interpreting results from an IMPACT run: Projections from the 2022 Global Food Policy Report; 4. Interpreting results from an IMPACT run: Tanzania analysis; 5. Climate models and IMPACT; 6. Processed-based Crop Simulation Modeling in Support of IMPACT; 7. Hands-on training exercises with IMPACT.